Respuesta :

Answer:

D) |–13| = 13

Step-by-step explanation:

[tex]- |13| = 13 : \mathrm{False}\\\\\mathrm{Simplify\:}-\left|13\right|:\quad -13\\-13=13\\[/tex]

Option B

[tex]\left|13\right|=-13\quad :\quad \mathrm{False}\\\mathrm{Simplify\:}\left|13\right|:\quad 13\\13=-13[/tex]

Option C

[tex]-\left|-13\right|=13\quad :\quad \mathrm{False}\\\mathrm{Simplify\:}-\left|-13\right|:\quad -13\\-13=13[/tex]

Option D

[tex]\left|-13\right|=13 ; True\\\mathrm{Apply\:absolute\:rule}:\quad \left|-a\right|=a\\\left|-13\right|=13\\\\13=13[/tex]